Measurement of the ZZ Production Cross Section in pp Collisions at sqrt[s]=13 TeV with the ATLAS Detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (Physical review letters, 2016)
The ZZ production cross section in proton-proton collisions at 13 TeV center-of-mass energy is measured using 3.2 fb^{-1} of data recorded with the ATLAS detector at the Large Hadron Collider. The considered Z boson candidates decay to an electron or muon pair of mass 66-116 GeV. The cross section is measured in a fiducial phase space reflecting the detector acceptance. It is also extrapolated to a total phase space for Z bosons in the same mass range and of all decay modes, giving 16.7_{-2.0}^{+2.2}(stat)+0.9/-0.7(syst)+1.0/-0.7(lumi) pb. The results agree with standard model predictions.